2010
DOI: 10.1111/j.1365-2788.2010.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of intellectual assessments over video conferencing and in‐person for individuals with ID: preliminary data

Abstract: Video conferencing administration does not appear to alter test results significantly for overall score on a brief intelligence test or a test of visual-motor integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 7 publications
2
40
0
Order By: Relevance
“…Visual impairments were assessed by the Beery-Buktenica Developmental Test of Visual-Motor Integration (Beery VMI) (7678), by standard clinical tests for visual acuity (Snellen chart) (79) and visual fields (confrontation and if in question, Goldman or Humphrey visual field testing) (80). Participants were also assessed for hemi-spatial neglect via the Schenkenberg’s line bisection test (81) and the single-letter cancelation test (82).…”
Section: Methodsmentioning
confidence: 99%
“…Visual impairments were assessed by the Beery-Buktenica Developmental Test of Visual-Motor Integration (Beery VMI) (7678), by standard clinical tests for visual acuity (Snellen chart) (79) and visual fields (confrontation and if in question, Goldman or Humphrey visual field testing) (80). Participants were also assessed for hemi-spatial neglect via the Schenkenberg’s line bisection test (81) and the single-letter cancelation test (82).…”
Section: Methodsmentioning
confidence: 99%
“…Remote cognitive assessment of adult-onset dementias by telephone or videoconferencing has been demonstrated to be as accurate as in-person evaluation and correlates well with standard cognitive assessments such as the Mini-Mental Status Exam. 22,23 Telemedicine delivery of health care is also rated by patients and caregivers as satisfactory 24,25 In addition, remote assessment has been used to obtain estimates of cognitive function in intellectually disabled adults - Temple et al 26 found on average only one Intelligence Quotient point difference between remote versus in-person evaluations, which is negligible. There is less known about remote cognitive assessment of children.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade there has also been increased emphasis on providing social and health care resources in the North where remote communities (often aboriginal or Inuit) can sometimes be accessed only by plane. Researchers in Ontario recently demonstrated that clinical assessments conducted through videoconferencing are valid and cost-efficient ways of addressing the clinical concerns of adults with IDD (Temple, Drummond, Valiquette, & Jozsvai, 2010).…”
Section: Aboriginal Healthmentioning
confidence: 99%